1994
DOI: 10.1002/nadc.19940420913
|View full text |Cite
|
Sign up to set email alerts
|

Spurenelementbestimmung in Baumringen mittels Laser‐ICP‐MS

Abstract: Mit Hilfe der Baumringanalytik sollte es möglich sein, den Verlauf außergewöhnlicher Umwelteinwirkungen, wie z.B. Klimaänderungen und Schadstoffdepositionen, zu rekonstruieren. Die Laserverdampfung der Festprobe mit einem induktiv gekoppelten Plasma als Ionenquelle für ein Massenspektrometer (Laser‐ICP‐MS) gestattet ohne chemische Vorbehandlung die direkte Analyse einzelner Baumringe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Latewood in this diffuse porous wood is less pronounced than in many other species, particularly conifers and other ring porous species like oak. More detailed studies, conducted as part of the present research, have shown that the large difference in element concentration found between latewood and earlywood in oak (21) is not evident in Acer.…”
Section: Resultsmentioning
confidence: 45%
“…Latewood in this diffuse porous wood is less pronounced than in many other species, particularly conifers and other ring porous species like oak. More detailed studies, conducted as part of the present research, have shown that the large difference in element concentration found between latewood and earlywood in oak (21) is not evident in Acer.…”
Section: Resultsmentioning
confidence: 45%